Factors contribute misconceptions towards Takaful insurance amongst customers of Bank Rakyat Gong Badak / Nurul Izani Mohammad - Mohammad, Nurul Izani (2011)
Today, insurance or Takaful sector has become more competitive in Malaysia. All insurance and Takaful companies are competing with each others in providing the best product and service to their existing and new customer. So, they try to provide the best service, quality, product features and make a great promotion in order to make their product can compete with other’s products. The objective of this research is to study the main factor that make misconceptions issues occurred towards Takaful amongst customers of Bank Rakyat. This research carried out about 100 respondents that enter into Bank Rakyat premise. These respondents are the walk-in customers that want to make any transaction and also that want to apply personal loan provided by Bank Rakyat. The factors that have been considered as for the misconceptions occur towards Takaful are knowledge of people, personal influence, and even the attitude of the customer itself. The researcher use the reliability analysis, frequency distribution and regression to determine what is the main factor that make the issue of misconceptions towards Takaful occurred amongst the customers of Bank Rakyat. Recommendations are also been given as to eliminate the issues of misconceptions toward Takaful in future.